National Snakebite Strategy of Bangladesh - Amin, Md Robed; Chowdhury, Nusaer; Chakraborty, Ashim; Faiz, Md Abul (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Abstract not available J Bangladesh Coll Phys Surg 2025; 43: 239-242